Real-time polymerase chain reaction in recurrent cytomegalovirus anterior uveitis - Rao, Vinita Girish (Am J Ophthalmol Case Rep, 2019)
PURPOSE: Cytomegalovirus (CMV) has been reported to cause anterior uveitis in the immunocompetent people. Recurrence of this viral uveitis poses a mangement dilemma. With real-time polymerase chain reaction(PCR), it is possible to confirm the clinical diagnosis. We report a case of recurrent CMV anterior uveitis documented by real-time PCR. OBSERVATIONS: A 42 year old man developed PCR proven CMV anterior uveitis. It resolved with oral and topical antivirals but recurred after ten months. The recurrence was controlled by restarting the oral antivirals. Real-time PCR was used to sequentially document the inital infection, the subsequent resolution and the recurrence of the infection. CONCLUSIONS AND IMPORTANCE: Real-time PCR is a useful tool in the management of CMV anterior uveitis.